Synthesis and characterization of intercalated nanocomposites based on poly(methacrylic acid) hydrogel and nanoclay cloisite-Na+ for possible application in agriculture - Junior, Carlos R. F. [UNESP]; De Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (American Scientific Publishers, 2017)
In this paper, poly(methacrylic acid)/Cloisite-Na+ (PMAA/Clay) nanocomposite hydrogels crosslinked by N,N'-methylene bisacrylamide (MBAAm) were synthesized via free radical polymerization using potassium persulfate (K2S2O8) as initiator. The spectroscopic and structural properties were investigated by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), respectively. It was studied in detail the effects of the nanoclay concentration, presence of salts and change of ionic charge in the hydrophilic properties by swelling degree (Q) measurements. The results indicated possible interaction between the nanoclay and the polymer, and the intercalation of the nanoclay sheets into polymeric matrix. The swelling degree of the nanocomposite hydrogels was controlled by presence of the nanoclay and by external swelling media, what is very required to different applications. From water absorption results and by controlling of hydrophilic and kinetic properties, nanocomposite hydrogels are promising candidates to future application as carrier vehicles for controlled release systems in the agriculture.
Keywords: Cloisite-Na+ nanoclay; FTIR; Hydrogel; Nanocomposite; Swelling degree; XRD